Incorporation of oleaster (Elaeagnus angustifolia L.) flour into white bread as a source of dietary fibers - Yavuz, Zeynep; Kutlu, Gozde; Tornuk, Fatih (WILEY, 2022)
The purpose of this work was to design a bread rich in dietary fibers and other bioactive compounds by the addition of oleaster flour (OF) at varying concentrations (0%, 5%, 10%, and 15% [w:w]) into the bread formulation. For this purpose, the physicochemical, textural, and sensorial properties of the resulting bread samples were analyzed during a storage period of 5 days. The addition of OF into the formulation provided higher (p < .05) moisture and ash contents to the bread. In comparison with the control sample, the addition of 5% (w/w) of OF increased the bread volume; however, the volume was negatively affected by higher OF levels. Texture profile analysis showed that 5% (w/w) of OF supplementation provided softer (p < .05) loaves while hardness was significantly (p < .05) increased during the storage. Increasing OF ratio resulted in darker (p < .05) crumb and crust color. Sensory evaluation revealed that OF-added bread samples all had acceptable scores in terms of all parameters. The current study demonstrated that OF could be successfully incorporated into white bread formulations to improve their nutritional properties without negatively affecting their physicochemical, textural, and sensorial properties. Novelty impact statement center dot Oleaster flour was used as a dietary fiber source in bread. center dot Influence of oleaster flour on bread quality was assessed. center dot The bread with 5% (w/w) of oleaster flour had the highest bread volume. center dot Darker bread crust and crumb was observed by elevating oleaster flour ratios. center dot Addition of oleaster flour did not negatively affect textural and sensory attributes.
Keywords: WHEAT-FLOUR; SENSORY ACCEPTABILITY; QUALITY; DOUGH; FUNCTIONALITY; ENRICHMENT; ACCEPTANCE; STORAGE; IMPACT; STARCH; Food Science & Technology